Implications of international cooperation on environmental protection: The case of agricultural sector of Mexico - Gallardo, A. H.; Gallardo, R. L. H.; Dias, Á.; Zarco, R. O.; Pereira, L. (International Journal of Agricultural Resources, Governance and Ecology, 2021)
The purpose of this research is to disclose the need of the developing countries of economic, technological and training resources to be able to show progress in the mitigation and adaptation of the States: the case of Mexico and its agricultural sector. Using a qualitative research design under Pattacini and Weisstaub (2009) regarding international cooperation as a key element for the countrys modernisation, also with the support of the ideology of Keohane and Nye regarding complex interdependence. It is observed that despite Mexico has implemented a normative and institutional platform, there are still some isolated sectors such as the agricultural which requires the application of new production processes through new technologies, innovation, and training.